Interactive Metadiscourse in Abstract of English Linguistics Research Articles - Ahmad Najib Mutawally; Elvi Citraresmana; Heriyanto Heriyanto (Universitas Muhammadiyah Prof. DR. HAMKA, 2019)
This research aims to study the use of Interactive Metadiscourse in Abstract Section of English Linguistics Reseach Articles. This reseach will use metadiscourse theory from Hyland (2005) which devide metadiscourse into two, they are textual and interpersonal metadiscourse, while interactive metadiscourse is part of interpersonal metadiscourse. This research also aims to find the frequentative forms of interactive metadiscourse and describe the function of each category of interactive metadiscourse. The findings showed that there are just three sub category of interactive metadiscourse found in 15 abstracts, they are frame markers, code glosses and trasition markers. The highest markers that is found in this reseach is the transtion markers with the word “and” which are appeared 84 times in 15 abstracts.